Patient Satisfaction With Telemedicine During the COVID-19 Pandemic: Retrospective Cohort Study - Ramaswamy, Ashwin; Yu, Miko; Drangsholt, Siri; Ng, Eric; Culligan, Patrick J; Schlegel, Peter N; Hu, Jim C (JMIR Publications, 2020)
BackgroundNew York City was the international epicenter of the COVID-19 pandemic. Health care providers responded by rapidly transitioning from in-person to video consultations. Telemedicine (ie, video visits) is a potentially disruptive innovation; however, little is known about patient satisfaction with this emerging alternative to the traditional clinical encounter. ObjectiveThis study aimed to determine if patient satisfaction differs between video and in-person visits. MethodsIn this retrospective observational cohort study, we analyzed 38,609 Press Ganey patient satisfaction survey outcomes from clinic encounters (620 video visits vs 37,989 in-person visits) at a single-institution, urban, quaternary academic medical center in New York City for patients aged 18 years, from April 1, 2019, to March 31, 2020. Time was categorized as pre-COVID-19 and COVID-19 (before vs after March 4, 2020). Wilcoxon-Mann-Whitney tests and multivariable linear regression were used for hypothesis testing and statistical modeling, respectively. ResultsWe experienced an 8729% increase in video visit utilization during the COVID-19 pandemic compared to the same period last year. Video visit Press Ganey scores were significantly higher than in-person visits (94.9% vs 92.5%; P<.001). In adjusted analyses, video visits (parameter estimate [PE] 2.18; 95% CI 1.20-3.16) and the COVID-19 period (PE 0.55; 95% CI 0.04-1.06) were associated with higher patient satisfaction. Younger age (PE -2.05; 95% CI -2.66 to -1.22), female gender (PE -0.73; 95% CI -0.96 to -0.50), and new visit type (PE -0.75; 95% CI -1.00 to -0.49) were associated with lower patient satisfaction. ConclusionsPatient satisfaction with video visits is high and is not a barrier toward a paradigm shift away from traditional in-person clinic visits. Future research comparing other clinic visit quality indicators is needed to guide and implement the widespread adoption of telemedicine.